Dual use of hematopoietic and mesenchymal stem cells enhances engraftment and immune cell trafficking in an allogeneic humanized mouse model of head and neck cancer. Issue 11 (3rd September 2018) - Morton, John J.; Keysar, Stephen B.; Perrenoud, Loni; Chimed, Tugs‐Saikhan; Reisinger, Julie; Jackson, Brian; Le, Phuong N.; Nieto, Cera; Gomez, Karina; Miller, Bettina; Gao, Dexiang; Somerset, Hilary; et al.
Abstract : In this report, we describe in detail the evolving procedures to optimize humanized mouse cohort generation, including optimal conditioning, choice of lineage for engraftment, threshold for successful engraftment, HNSCC tumor implantation, and immune and stroma cell analyses. We developed a dual infusion protocol of human hematopoietic stem and progenitor cells (HSPCs) and mesenchymal stem cells (MSCs), leading to incremental human bone marrow engraftment, and exponential increase in mature peripheral human immune cells, and intratumor homing that includes a more complete lineage reconstitution. Additionally, we have identified practical rules to predict successful HSPC/MSC expansion, and a peripheral human cell threshold associated with bone marrow engraftment, both of which will optimize cohort generation and management. The tremendous advances in immune therapy in cancer have made the need for appropriate and standardized models more acute than ever, and therefore, we anticipate that this manuscript will have an immediate impact in cancer‐related research. The need for more representative tools to investigate the human tumor microenvironment (TME) has led to the development of humanized mouse models. However, the difficulty of immune system engraftment and minimal human immune cell infiltration into implanted xenografts are major challenges. We have developed an improved method for generating mismatched humanized mice (mHM), using a dual infusion of human HSPCs and MSCs, isolated from cord blood and expanded in vitro. Engraftment with both HSPCs and MSCs produces mice with almost twice the percentage of human immune cells in their bone marrow, compared to mice engrafted with HSPCs alone, and yields 9‐ to 38‐fold higher levels of mature peripheral human immune cells. We identified a peripheral mHM blood human B cell threshold that predicts an optimal degree of mouse bone marrow humanization. When head and neck squamous cell carcinoma (HNSCC) tumors are implanted on the flanks of HSPC‐MSC engrafted mice, human T cells, B cells, and macrophages infiltrate the stroma of these tumors at 2‐ to 8‐fold higher ratios. In dually HSPC‐MSC engrafted mice we also more frequently observed additional types of immune cells, including regulatory T cells, cytotoxic T cells, and MDSCs. Higher humanization was associated with in vivo response to immune‐directed therapy. The complex immune environment arising in tumors from dually HSPC‐MSC engrafted mice better resembles that of the originating patient's tumor, suggesting an enhanced capability to accurately recapitulate a human TME.